2016
DOI: 10.1016/j.rse.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the influences of spectral resolution on uncertainty in leaf trait estimates through a Bayesian approach to RTM inversion

Abstract: The remote monitoring of plant canopies is critically needed for understanding of terrestrial ecosystem mechanics and biodiversity as well as capturing the short-to long-term responses of vegetation to disturbance and climate change. A variety of orbital, sub-orbital, and field instruments have been used to retrieve optical spectral signals and to study different vegetation properties such as plant biochemistry, nutrient cycling, physiology, water status, and stress.Radiative transfer models (RTMs) provide a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 80 publications
3
72
0
Order By: Relevance
“…(see Methods S3 for more details). Similar to Shiklomanov et al (2016), we found strong agreements between measured and modeled transmittance, in terms of both mean values and standard deviation (Fig. S5a).…”
Section: Ground Observationssupporting
confidence: 80%
See 3 more Smart Citations
“…(see Methods S3 for more details). Similar to Shiklomanov et al (2016), we found strong agreements between measured and modeled transmittance, in terms of both mean values and standard deviation (Fig. S5a).…”
Section: Ground Observationssupporting
confidence: 80%
“…Shiklomanov et al . () showed that PROSPECT‐inverted leaf transmittance is highly consistent with values obtained with an integrating sphere for fresh leaves. As a check, we compared our estimated transmittance against a set of independent measurements made in 2002 by T.M.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…optical, LiDAR) from the leaf to landscape are used to inform the RTM structure and to parameterize across spatial and temporal scales (e.g. Shiklomanov et al ., ).
Recommendations: (17) TBMs should not use single layer big leaf models. (18) We need better model representation of canopy architecture and vertical scaling of foliar properties, and data to evaluate alternative radiative transfer models and scaling approaches.
…”
Section: Scaling Physiologymentioning
confidence: 99%